LEGALITAS WILAYAH TERITORIAL AUSTRALIA DI BENUA ANTARTIKA DALAM PENANGKAPAN IKAN PAUS DI AUSTRALIAN ANTARCTIC TERRITORY BERDASARKAN UNCLOS 1982 : Legality Of Australian Territory In The Antarctic Continent In Whaling The Australian Antarctic Territory Based On UNCLOS 1982 - Harris Novyar Rages; Amalia Zuhra (Faculty of Law, Universitas Trisakti, 2024)
Japan through the JARPA program (Japanese Whale Research Program under Special Permit in the Antarctic) from 1987-2005 applied for a special permit to conduct whaling to the International Whaling Commission (IWC). In 2005 Japan resumed the JARPA program through the Second Phase of the Japanese Whaling Research Program under Special Permit in the Antarctic (JARPA II) policy. Related to this, the problem formulation of this article is: Is the territorial area owned by Australia on the Antarctic continent in accordance with the 1959 Antarctic Treaty? Then, how is the implementation of the principle of common heritage of mankind by Australia in the case of JARPA II? The type of research used in writing this article is normative juridical and the data used is secondary data, and the way of drawing conclusions in this research is done deductively. The Results of this research is that the claim owned by Australia in the AAT is valid, because based on its history, Australia already owned the area long before the ratification of the 1959 Antarctic Treaty. Furthermore, the conclusion is the country has actively sought to protect and promote the sustainability of natural resources in the AAT.